Is chronic obstructive pulmonary disease a risk factor for erectile dysfunction? A cross-sectional, comparative study - Hamada Kawshty; Mahmoud A.S Makki; Walid A Elmorsy; Maher A Shabaan; Ahmad A Ahmad (Wolters Kluwer Medknow Publications, 2019)
Background Sexual dysfunction is a common problem in chronic obstructive pulmonary disease (COPD). Aim To evaluate the sexual activity in patients with COPD. Patients and methods A total of 100 male patients with COPD (diagnosed and staged according to the American Thoracic Society guidelines) and 96 healthy volunteers (controls) with normal pulmonary function were included. After clinical evaluation, pulmonary function test, arterial blood gas, and hormonal profiles such as follicle-stimulating hormone, leutenizing hormone, and testosterone (total and free) were measured and compared. Participants were asked to answer the International Index of Erectile Function questionnaire as a method to diagnose and classify impotency. Results Varying degrees of erectile dysfunction (ED) was detected in 78 (78%) patients with COPD and 56 (58.3%) of controls. The mean score of ED was found to be significantly (P<0.000) lower in comparison with the controls with significantly correlated with age, smoking index, percentage of forced expiratory volume in the first second, percentage of forced vital capacity, FEV/EVC ratio, PaO2, PaCO2, oxygen saturation (SaO2), total testosterone, and 6-min walk test. The smoking index, PaCO2, follicle-stimulating hormone, and leutenizing hormone were found to be significantly higher in patients with COPD compared with controls whereas percentage of forced expiratory volume in the first second, percentage of forced vital capacity, PaO2, SaO2, and BMI were significantly lower in patients with COPD. The results of 6-min walk test test between the two groups reveal highly significant decrease in physical fitness in patients with COPD than normal controls. Conclusion ED is a frequent problem in patients with COPD. Hypoxemia, smoking, limitation of physical activity, and hormonal imbalance are thought to be responsible mechanisms for ED in patients with COPD.